The Effect of Intellectual Capital on Knowledge Management with the Mediating Role of Organizational Commitment - Seyed Ahmad Hosseini Golafshani; Forough Amir Malayeri (Pascasarjana UM, 2018)
Abstract: For many years, at the competitive examination, Yazd province students have the highest acceptance rate to enter university. The attention to knowledge management and its impact in the creation of an intangible capital type (but vital) called intellectual investment among employees and institutional managers responsible to educate are an indispensable necessity in the education department of Yazd province. In this regard, the present study was conducted with the aim of investigating the effect of intellectual capital on knowledge management with the interceding role of organizational commitment in the General Office of Education in Yazd province, Iran. The results showed that intellectual capital affects knowledge management and intellectual capital is imperative for organizational commitment. Organizational commitment influences knowledge management. Organizational commitment has a significant positive mediation effect in the influencing of intellectual capital on knowledge management.Key Words: intellectual capital, knowledge management, organizational commitment, knowledge creation, knowledge sharingAbstrak: Bertahun-tahun, pada ujian kompetitif, siswa provinsi Yazd memiliki tingkat penerimaan tertinggi untuk masuk ke universitas. Perhatian terhadap manajemen pengetahuan dan dampaknya dalam penciptaan modal tidak berwujud (tetapi vital) yang disebut investasi intelektual di antara karyawan dan manajer institusional yang bertanggung jawab untuk mendidik adalah kebutuhan yang sangat diperlukan di departemen pendidikan provinsi Yazd. Penelitian dilakukan dengan tujuan menyelidiki efek modal intelektual pada manajemen pengetahuan dengan peran menjadi perantara komitmen organisasi di Departemen Pendidikan provinsi Yazd, Iran. Hasil penelitian menunjukkan bahwa modal intelektual mempengaruhi manajemen pengetahuan dan modal intelektual sangat penting untuk komitmen organisasi. Komitmen organisasi mempengaruhi manajemen pengetahuan. Komitmen organisasi memiliki efek mediasi positif yang signifikan dalam mempengaruhi modal intelektual pada manajemen pengetahuan.Kata kunci: modal intelektual, manajemen pengetahuan, komitmen organisasi, penciptaan pengetahuan, penyebaran pengetahuan